Problematising unfocused written feedback: A case study on four university students’ essays - Journal, ILS (Issues in Language Studies, 2015)
In the past decade, many studies have sought to show the efficacy of different types of written feedback. All of these studies yielded consistent results, and at times contradicting results. Considering the nature of language teaching and learning, English language teaching (ELT) practitioners should consider problematising the issue of providing written feedback, instead of looking for a solution. Taking this into account, this study uses a case-study approach to evaluate the efficacy of unfocused feedback across multiple-drafts in an advanced English writing course taken by English majors at an international university in Thailand. Over a four-month semester, the class wrote five essays, with each essay having at least three drafts. In all drafts, unfocused feedback was provided with the assumption that students’ prior English writing courses have helped them develop self-monitoring abilities. The data consist of the frequency of errors and unfocused feedback of the last three essays of four students. Subsequently, a correlation coefficient of the errors and unfocused feedback was calculated and results indicated that as the number of feedback decreased through drafts, the number of errors decreased as well. This shows a positive correlation between the two variables, albeit at varying degrees for different students. Students were also interviewed about their perceptions and expectations toward writing feedback. This study suggests that unfocused feedback may work for certain students, but not all.